The Relationship of Muhadharah Activities with Student Learning Outcomes in the Akidah Akhlak Subject - Hikam, Bahrul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The aim of this research is to determine the relationship between muhadharah activities and student learning outcomes in akidah and morals subjects at Madrasah Tsanawiyah Daarul Ahsan Tangerang. Because Akidah Akhlak is a foundation or basis that must be instilled in students in order to become ethical and civilized. humans in their daily lives. This research uses a quantitative descriptive approach. Researcher using correlational methods (methods that look for relationships or correlations between the variables being searched for) which are supported by data and facts through questionnaires/questionnaires distributed. The population taken was all students of Madrasah Tsanawiyah (MTs) Daarul Ahsan Tangerang, totaling 150 people. Regarding sampling techniques, the author uses the "Purposive Sampling" technique. In this study, the samples taken were 30 class VIII students. The data collection techniques used are observation, questionnaires and documentation. In data analysis techniques, researchers decided to use statistical calculation analysis techniques. The research used the data analysis technique used, namely the product moment technique. Then finally a hypothesis test is carried out. The results of this research prove that between muhadharah activities (variable 0.80). This means that the relationship between muhadharah activities (Further variable, based on the results of the product moment calculation "r" it is known that tcount= 18 > ttable=1.70 Ha is accepted. This means that there is a significant relationship between muhadharah activities and student learning outcomes in the subject of Akidah Akhlak.